The impact of life events on person-centred personality consistency - Wright, Amanda; Jackson, Joshua (My University, 2022)
Few environments reliably influence mean-level and rank-order changes in personality – perhaps because personality development needs to be examined through an individualized, person-centered lens. The current study used Bayesian multilevel linear models to examine the impact of life events on changes in ipsative consistency across four to 10 waves of data with four datasets (N = 24,491). Both between- and within-person effects were found for various life events. Selection effects were found for events such as marriage, (un)employment, retirement, and volunteering whereas between-person effects for slopes were found for events such as widowhood, beginning schooling, employment, and retirement. Within-person changes, when present, were typically brief and negative, suggesting life events serve as a short-term disruption to the personality system. However, there were many individual differences around event-related trajectories. Our results highlight that the effects of life events depend on how personality, and changes in it, are quantified – with these findings underscoring the utility of a person-centered approach as it can capture the full range of these idiosyncrasies. Overall, these findings suggest that life events have differential impacts on people and that life events can serve as a short-term, destabilizing shock to one’s personality system.
Keywords: Families and relationships; Health and wellbeing; Lifestyle